2018
DOI: 10.1080/00365521.2018.1531653
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment patterns, resource use and costs of treating uncontrolled carcinoid syndrome and carcinoid heart disease: a retrospective Swedish study

Abstract: Objectives: To quantify healthcare resource use (HRU) and costs in relation to carcinoid syndrome (CS) and carcinoid heart disease (CHD) in a real-world setting, and to provide perspective on treatment patterns. Materials and methods: Patient data and HRU were collected retrospectively from three Swedish healthcare registers. Adult patients diagnosed with metastatic gastroenteropancreatic neuroendocrine tumors (GEP-NETs) grade 1 or 2 and CS who purchased somatostatin analogs (SSAs), and experienced controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…One study captured by this review reported improvements to patient QoL after undergoing differential diagnosis of diarrhoea, and other studies have shown that a higher number of bowel movements are associated with lower QoL in patients with GEP-NETs[ 7 , 75 ]. Furthermore, a real-world evidence study reported that total healthcare resource use costs increased with uncontrolled CS in patients with GEP-NETs by up to 40% per patient, when compared with controlled CS[ 76 ]. This highlights an important opportunity for improving QoL in patients with GEP-NETs and efficient use of clinical resources; identifying the true cause(s) of diarrhoea may facilitate optimal symptom control through targeted management.…”
Section: Discussionmentioning
confidence: 99%
“…One study captured by this review reported improvements to patient QoL after undergoing differential diagnosis of diarrhoea, and other studies have shown that a higher number of bowel movements are associated with lower QoL in patients with GEP-NETs[ 7 , 75 ]. Furthermore, a real-world evidence study reported that total healthcare resource use costs increased with uncontrolled CS in patients with GEP-NETs by up to 40% per patient, when compared with controlled CS[ 76 ]. This highlights an important opportunity for improving QoL in patients with GEP-NETs and efficient use of clinical resources; identifying the true cause(s) of diarrhoea may facilitate optimal symptom control through targeted management.…”
Section: Discussionmentioning
confidence: 99%
“…To incorporate CaHD into the model, the following assumptions were made: an increase in 5-HIAA levels is associated with an increase in CaHD incidence; TE reduces 5-HIAA levels regardless of durable response status [38]; and individuals with CaHD have an increased risk of death compared with those [38], in which 20 of 45 (44.4%) patients randomised to SSA + TE demonstrated a durable response, compared with 9 of 45 (20%) patients randomised to SSA + placebo; therefore, for the purpose of this model, 24.4% of the response was presumed to be attributable to TE d Values from Lesén et al [33], which cover an 8-month period, were divided by eight to determine per-month costs e Annual CaHD incidence was assumed to be 2.96% for patients with 5-HIAA < 300 mmol/24 h [50] f TE not included in standard of care…”
Section: Model Inputsmentioning
confidence: 99%
“…Patients in the SSA + TE arm during the initial treatment period and those in the durable response and inadequate response to TE health states within the Markov model incurred this cost. Real-world CS and CaHD-related costs, including healthcare resource use (frequency per month), drug acquisition and SSA dosage (cost of average dose) for patients with controlled and uncontrolled CS were obtained from a retrospective Swedish database study [33] (Table 1). A number of symptoms not limited to diarrhoea may contribute to cost differences between responders and non-responders in the model.…”
Section: Cost Inputsmentioning
confidence: 99%
See 2 more Smart Citations